Ecoinovaç\~ao no Brasil: O desempenho das empresas brasileiras no período 2000-2017 - Pedro Miranda; Priscila Koeller; Maria Cecília Junqueira Lustosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The role of eco-innovation as central element for reversal of environmental degradation resulting from anthropogenic action and for implementation of a sustainable development model has been reiterated by the literature and by international institutions and forums. Public policies encouraging investment in eco-innovations, such as tax incentives and environmental regulation, are increasingly important. The development and evaluation of such instruments, in turn, cannot do without the characterization of the performance of eco-innovation agents. However, the lack of statistics on eco-innovation is still a major obstacle. In this context, this work aims to characterize eco-innovation in companies in Brazil based on information available in the Innovation Survey, in patent applications documents, and in data from the companies concession of international certification. The results showed a worrisome scenario, in which a small number of economic activities stands out as eco-innovators and most of them registered worsening indicators in recent years.
Keywords: Q01; Q55; Q56; 330; eco-innovation; environmental innovation; green technologies